Daniel Cottier's Aesthetic of Beauty in Australia - Montana, Andrew (Australasian Journal of Victorian Studies, 2019)
As well as establishing decorating firms in London and New York, Daniel Cottier (1837-91) co-founded the Australian decorating firm, Lyon, Cottier & Co. in 1873 with John Lamb Lyon (1835-1916), who moved from Melbourne to Sydney to open the branch. This article examines Lyon, Cottier & Co.’s early work, hitherto not known to many Victorian studies scholars, through its study of significant commissions and patrons and the direct influence of Cottier’s stylistic approach on the decorative art of the Australian firm between 1873 and circa 1880. The beautification of interiors with figures illustrating types from the Old and New Testaments surrounded by flora and ornaments was seen in churches throughout New South Wales as early as 1875. Conventionalised ornaments inspired by nature, the medieval and ancient worlds and allegorical maidens representing the Seasons and Night and Day adorned the ceilings, walls and the windows of private residences. Cottier’s work went on to translate the spirit of Pre-Raphaelitism with modern vigour into new and powerful works of Aesthetic decorative art in Australia, fusing the spirits of Hebraism (morality) and Hellenism (aesthetic taste) with the alluring qualities of sweetness and light as ensigns of beauty in the architectural ornamental arts.